2010
DOI: 10.1177/0310057x1003800213
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Tryptophan Catabolism Along the Kynurenine Pathway Precedes Ongoing Sepsis in Critically Ill Patients

Abstract: It has recently been shown that an increased plasma level of the tryptophan catabolite kynurenine is an early indicator for the development of sepsis in major trauma patients. We examined the predictive value of kynurenine pathway activity for ongoing sepsis in patients being admitted to a surgical intensive care unit for different reasons. In addition, we asked whether an accumulation of kynurenines in patients' plasma depends on reduced renal clearance. We conducted a prospective observational study includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 29 publications
3
41
1
Order By: Relevance
“…KYNA has been also suggested as a marker of distress intolerance (Chiapelli et al 2014). Noteworthy, increasing plasma KYNA concentration might predispose to sepsis and septic shock in patients after multi trauma and its level is related to sseverity of infection (Dabrowski et al 2014; Schefold et al 2009; Zeden et al 2010). All of the above-mentioned pathologies may complicate early postoperative period in cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KYNA has been also suggested as a marker of distress intolerance (Chiapelli et al 2014). Noteworthy, increasing plasma KYNA concentration might predispose to sepsis and septic shock in patients after multi trauma and its level is related to sseverity of infection (Dabrowski et al 2014; Schefold et al 2009; Zeden et al 2010). All of the above-mentioned pathologies may complicate early postoperative period in cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Raised blood KYNA has been found in septic patients (Dabrowski et al 2014; Schefold et al 2009; Zeden et al 2010), HIV-1 infection (Heyes et al 1992), chronic kidney disease (Schefold et al 2009), stroke patients (Darlington et al 2007), after severe brain injury (Mackay et al 2006) and cardiac arrest (Ristagno et al 2013). Moreover, increased salivary KYNA concentration has been observed after acute physiological stress (Chiapelli et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurotoxic capacity of QuinA in vivo has implicated it in a variety of neurodegenerative disorders, including Huntington's disease [23,26,27] and Alzheimer's disease [28]. Moreover, QuinA is increased in clinical conditions such as renal dysfunction [29] and sepsis [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Zeden et al conducted a prospective study quantifying tryptophan and its metabolites. Their results demonstrated that plasma concentrations of quinolinic acid and the quinolinic acid/tryptophan ratio displayed the best discrimination between nonseptic and preseptic patients [15].…”
Section: Introductionmentioning
confidence: 99%